食口論: 현대 한국사회에서의 음식관습 - 주영하(Joo Young-ha) (한국학(구 정신문화연구), 2002)
As one of the fundamental elements for a human life, a food plays a very primitive role in managing the human body in biological terms. However, cultural factors always affect the supply and demand of food, such as in ingredient preparation, recipe selection, table manners, and food distribution, etc. Consequently, the cultural aspect of food can become an important research subject of folklore. This study is based on the assumption that today's foodtradition in Korea tends to be established by the Shik'gu, members of a family, within a house. It may be difficult to consider the word Shik'gu as an academic term. It can, however, be a useful term, that relates to the cultural behavior of a group of food consumers who live together. That is, Shik'gu also refers to a organization within which its members share food commensalism. Generally, a Shik'gu consists of a married couple and their children or relatively more members spanning three generations who reside in a city or in the country, respectively. In addition, this study revealed that the most Koreans define Shik'gu with its members some numbers between them. In other words, it is the former type of family considering its parents or grandparents as if they lived together. National holidays, sacrificial rites, family unions, etc., are the only time when they actually get together. Some Shik'gu groups share foods within this expanded family system: soy source, chilly pepper paste, soybean paste, kim-chi, etc. Usually, parents in the countryside distribute them to their children in cities. Therefore, although contemporary Korean society in the city is mostly made up of Shik'gu with a nuclear type few members, the fundamental idea of Shik'gu is based on the extended family system in the countryside. KCI Citation Count: 7